The Optimal Location and Compensation Level of Thyristor Controlled Series Compensator (TCSC) in Wholesale Electricity Markets considering Active Power Reserves - Pham, Nang Van; La, Minh Khanh (Old Journal, 2018)
In the electricity market operation, when the congestion in power systems appears, total system cost increases, making the difference of locational marginal prices on the branch becomes bigger and generators can have market power. One of the measures to overcome network congestion is using thyristor-controlled series capacitor (TCSC). In this paper, a method for determining the optimal location and control parameters of TCSC in the wholesale electricity market, which consists of price-sensitive loads and ancillary services related to frequency control has been suggested. The sensitive method based on performance index is employed to optimally locate TCSC. The TCSC compensation level is appraised by co-optimization technique of energy and active power reserves with an objective function to maximize social welfare and minimize investment cost of TCSC. Moreover, this work has also made a comparison between additional social welfare and the investment cost of TCSC. The calculated results are applied on the North power system in Vietnam.